GA based algorithms for offshore wind farm collector cable optimization - Ho, Wei-Chung (Journal of physics. Conference series, 2022)
In the capital-intensive offshore wind farm industry, the collector cable optimization problem arises primarily due to electric infrastructure expense contributing high rate of initial investment cost. In this study, a multistage solution was developed for optimal locations, the number of offshore substations (OSSs), and inter-array cable routing determination. In the first, a novel GA method picks up the initial OSSs number and location from the candidate site list, then capacities minimum span tree (CMST) is applied to identify valid cable routings. Finally, optimal OSSs location, quantity, and cable paths are obtained through an iterative process. The results of a library real wind farms case are introduced in paper proves the feasibility of the proposed method and showed this study can apply on real practice for optimal decision in OWF cable design.